2016
DOI: 10.1111/scs.12355
|View full text |Cite
|
Sign up to set email alerts
|

The role of religion and spirituality in coping with kidney disease and haemodialysis in Thailand

Abstract: Religion and spirituality provide powerful coping strategies that can help Thai people with CKD overcome the associated distress and difficulties. Religion and spirituality cannot be separated in Thai culture because Thai people are both religious and spiritual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
2
15
0
2
Order By: Relevance
“…The role of religion and spirituality in coping with kidney disease and haemodialysis in Thailand (38) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of religion and spirituality in coping with kidney disease and haemodialysis in Thailand (38) .…”
mentioning
confidence: 99%
“…Loureiro spiritual practices as a modality of coping, including religious and spiritual for the development of disease, karmic disease, merit, prayer and praises, and the act of bargaining with the gods through promises. Finally, the authors associated the results with the religiosity and spirituality of the Thai people (38) .…”
mentioning
confidence: 99%
“…Coping is referred to cognitive and behavioral responses to control stressors, both external and internal that can burden one's life [12]. Coping is a process used by someone to manage stress and handle stressful situations in life [12].…”
Section: Description Of Respondents' Coping Mechanisms Undergoing Hemmentioning
confidence: 99%
“…Coping is referred to cognitive and behavioral responses to control stressors, both external and internal that can burden one's life [12]. Coping is a process used by someone to manage stress and handle stressful situations in life [12]. Research results showed that knowledge, awareness, family, religion, and duration of illness are important factors influencing self-care and self-management.…”
Section: Description Of Respondents' Coping Mechanisms Undergoing Hemmentioning
confidence: 99%
“…Coping refers to the constant changes a person's cognitive and behavioral efforts to manage the demands of the specific needs of both external and internal burdensome or exceeding one's resources [20]. Researchers assumed that adaptive coping mechanisms in this study is shown by the efforts of respondents receiving hemodialysis and accustomed to the action, feeling depressed a little or sometimes perceived by respondents when undergoing hemodialysis therapy.…”
Section: Minimum-maximunmentioning
confidence: 99%